Experimental Investigations Of Oxygen Stripping from Feed Water in a Spray and Tray Type De-Aerator - K. V., Sharma; K. V., Suryanarayana; P. K., Sarma; M. M., Rahman; M. M., Noor; K., Kadirgama (Universiti Malaysia Pahang, 2010)
The influence of various parameters on oxygen stripping for a two stage spray and tray type de-aerator is analyzed experimentally. It is observed that increasing the mass flow rate of water leads to an increase in heat and mass transfer coefficients in both stages. There is no significant influence of de-aerator pressure and length of the second stage on the heat transfer coefficients in the range tested. The increase in de-aerator pressure enhances the mass transfer coefficient by 14 percent, whereas the increase in length of the second stage has no significant influence. The empirical correlations available in the literature predict the mass transfer coefficients satisfactorily in the experimental range tested. The total length of the de-aerator is a significant parameter influencing the quantity of oxygen removed from the feed water.